MicroRNA‐27b is a regulatory hub in lipid metabolism and is altered in dyslipidemia1234. Issue 2 (6th July 2012) - Vickers, Kasey C.; Shoucri, Bassem M.; Levin, Michael G.; Wu, Han; Pearson, Daniel S.; Osei‐Hwedieh, David; Collins, Francis S.; Remaley, Alan T.; Sethupathy, Praveen
Abstract Cellular and plasma lipid levels are tightly controlled by complex gene regulatory mechanisms. Elevated plasma lipid content, or hyperlipidemia, is a significant risk factor for cardiovascular morbidity and mortality. MicroRNAs (miRNAs) are posttranscriptional regulators of gene expression and have emerged as important modulators of lipid homeostasis, but the extent of their role has not been systematically investigated. In this study we performed high‐throughput small RNA sequencing and detected ≈150 miRNAs in mouse liver. We then employed an unbiased, in silico strategy to identify miRNA regulatory hubs in lipid metabolism, and miR‐27b was identified as the strongest such hub in human and mouse liver. In addition, hepatic miR‐27b levels were determined to be sensitive to plasma hyperlipidemia, as evidenced by its ≈3‐fold up‐regulation in the liver of mice on a high‐fat diet (42% calories from fat). Further, we showed in a human hepatocyte cell line (Huh7) that miR‐27b regulates the expression (messenger RNA [mRNA] and protein) of several key lipid‐metabolism genes, including Angptl3 and Gpam. Finally, we demonstrated that hepatic miR‐27b and its target genes are inversely altered in a mouse model of dyslipidemia and atherosclerosis. Conclusion: miR‐27b is responsive to lipid levels and controls multiple genes critical to dyslipidemia. (HEPATOLOGY 2013)